Development of narrative competences from bilingual children: The acquisition of Spanish in the german-speaking part of Switzerland. - Sánchez Abchi, Verónica (Swiss Journal of Educational Research, 2018)
The main goal of this study is to examine the oral versions of personal experiences produced by spanish/swiss german bilingual children. This work focuses on the bilingual childrens‘ capacities before the beginning of primary school, and examines the early development of narrative capacity which is an important precursor to literacy (Dickinson & Tabors, 2001). A total of 24 narratives produced by 3 and 5 years old children were analysed. A questionnaire was also distributed to the families, in order to know the linguistic practices at home and the childrens’ linguistic biographies. Results show developmental differences between the younger and older children. Besides, they also reveal a link between the linguistic practices in the family and the narrative performance. Moreover, some narrative capacities in Spanish that could also be transferred to the majority language are observed. Finally, we reflect on the conditions that promote the preservation of Spanish and its potential contributions to schooling.